Cerebral venous thrombosis: a changing landscape - Colaco, Vimala; Sundaramurthy, Harsha; Paneyala, Shasthara; C., Nemichandra S. (International Journal of Research in Medical Sciences, 2021)
Cerebral venous thrombosis (CVT) is an uncommon cause of stroke and is mainly a disease of the young. The aims of the study were to summarize the change in the clinical profile of CVT and provide an update regarding the current management of the same. A literature search was conducted using Pubmed and Google scholar using the desired terms. Studies were analysed and review was formulated. The median age of CVT in most studies was 32 years. There has been a shift from female pre-ponderence to equal gender predilection. Several studies are confirming the efficacy of D-dimer as a diagnostic marker of CVT. Newer oral anticoagulants have been found to be as efficient as warfarin. There have been several cases of CVT reported in association with COVID-19. This review confirmed the traditional understanding of age and risk factors of CVT. It also noted a change from the female pre-ponderence. NOACS are emerging as the preferred drug for the long-term management of CVT.